Lycopene attenuates Aβ1–42 secretion and its toxicity in human cell and Caenorhabditis elegans models of Alzheimer disease. (3rd November 2015) - Chen, Wei; Mao, Liuqun; Xing, Huanhuan; Xu, Lei; Fu, Xiang; Huang, Liyingzi; Huang, Dongling; Pu, Zhijun; Li, Qinghua
Highlights: Lycopene delayed the paralysis in the Aβ1–42 -transgenic Caenorhabditis elegans strain GMC101. Lycopene reduced Aβ1–42 secretion level in human SH-SY5Y cells. Lycopene down-regulated expression level of β-amyloid precursor protein(APP) in APPsw cells. Lycopene protected against H2 O2 -induced oxidative stress and copper-induced damage in APPsw cells. Abstract: Growing evidence suggests concentration of lycopene was reduced in plasma of patients with Alzheimer disease (AD). Lycopene, a member of the carotenoid family, has been identified as an antioxidant to attenuate oxidative damage and has neuroprotective role in several AD models. However, whether lycopene is involved in the pathogenesis of AD and molecular underpinnings are elusive. In this study, we found that lycopene can significantly delay paralysis in the Aβ1–42 -transgenic Caenorhabditis elegans strain GMC101. Lycopene treatment reduced Aβ1–42 secretion in SH-SY5Y cells overexpressing the Swedish mutant form of human β-amyloid precursor protein (APPsw). Next, we found lycopene can down-regulate expression level of β-amyloid precursor protein(APP) in APPsw cells. Moreover, lycopene treatment can not change endogenous reactive oxygen species level and apoptosis in APPsw cells. However, lycopene treatment protected against H2 O2 -induced oxidative stress and copper-induced damage in APPsw cells. Collectively, our data support that elevated lycopene contributes to the lower pathogenesis of AD. Our findings suggest that increasing lycopene in neurons may be a novel approach to attenuate onset and development of AD.